Ecological landscape design and planning : the Mediterranean context - Makhzoumi, Jala, 1949-; Pungetti, Gloria (E & FN Spon, 1999)
Based on both research and practical experience, Ecological Landscape Design and Planning offers a holistic methodological approach to landscape design and planning. It focuses on the scarcity of natural resources in the Mediterranean and the need to aim for long-term ecological stability and environmental sustainability. The principles of this approach, therefore, can be used as a theoretical foundation for holistic landscape research, creative ecological design and better sustainable practice development.